Densidade mineral óssea em adolescentes: contribuição da coorte de nascimentos de São Luís 1997/98 - ARAÚJO, Allanne Pereira (2022)
The accumulation of bone mass begins in fetal life, extends throughout childhood and has its peak in adolescence. Thus, it is important to assess the bone health of adolescents in order to prevent osteopenia / osteoporosis, diseases considered as public health issues of great economic impact. This thesis consists of two articles. In the first, the prevalence and factors associated with low bone mineral density (BMD) of adolescents among adolescents was estimated. This study was carried out with 2515 adolescents aged 18-19 years from the São Luís birth cohort of 1997/98. Cross-sectional study where sociodemographic conditions, lifestyle, sleep quality, physical activity and depression were studied. It was found that 0.8% of the adolescents had low BMD of the body, 0.9% had low BMD of the femoral head and 3.7% had low BMD of the lumbar spine. Male adolescents (p<0.001), attending elementary school (p<0.001), with an income of up to one minimum wage (p=0.015) and those considered physically inactive (p=0.017) had lower lumbar spine BMD. In the second article, the association between birth weight and BMD in adolescence was investigated. Cohort study, using data from two moments (birth and 18/19 years) from the research Coortes RPS. For the analysis of BMD, the Z-score index (whole body) measured by densitometry by double emission of X-rays was used. A theoretical model was constructed using the directed acyclic graphs and to evaluate the association between birth weight and BMD, regression was used. multiple linear. Of the 2112 adolescents, 8.2% had low birth weight and low BMD for age was 2.8%. The mean Z-score for the whole body was 0.19 (± 1.00). After adjustment, it was observed that the greater the weight at birth, the greater the BMD in adolescence (Coef .: 0.10; 95% CI: 0.02 - 0.18; p = 0.014). Birth weight appears to affect BMD in adolescence. Studies have shown that higher birth weight values were associated with higher BMD values for the whole body, and that male individuals, with high school education, family income of up to one minimum wage and those sedentary had lower BMD of the lumbar spine. These are important findings to support public health policies since a reduction in BMD is strongly associated with an increased risk of fracture and / or osteopenia / osteoporosis.